HUBUNGAN STRUKTUR AKTIVA DAN STRUKTUR FINANSIAL DENGAN KINERJA KEUANGAN PT. GARUDA INDONESIA (PERSERO) TBK. PERIODE 2016-2020 DITINJAU DARI PERSPEKTIF SYARIAH - Fakhruddin, Imam; Mabruroh, Rosyidatul; Firdaus, Firdaus (Program Studi Manajemen Keuangan Syariah, 2022)
The purpose of this study was to determine the relationship between asset structure and financial structure with financial performance as seen from the financial performance of PT. Garuda Indonesia. This type of research is associative research, namely research that connects two or more variables. The data used is secondary data in the form of financial statements of PT. Garuda Indonesia for the 2016-2020 period. The research method used is the Pearson correlation analysis method and hypothesis testing is done by testing the significance. The results showed that the asset structure and financial structure had a negative and significant relationship with the financial performance of PT. Garuda Indonesia. Based on these results obtained the value of the correlation coefficient (r) asset structure with the financial performance of PT. Garuda Indonesia is -0.957 indicating that the asset structure has a negative relationship (not direct) and has a high (r) correlation (-0.957 close to -1) with financial performance. And the financial structure with financial performance is at the value of PT. Garuda Indonesia is -0.257 indicating that the financial structure has a negative relationship (not direct) and has a high (r) correlation (-0.257 close to -1) with financial performance.